Assessment, reinforcement and monitoring of timber structures: FPS Cost Action FP1101 - D’Ayala, Dina (2014)
Interest in extending the life of existing and historic timber structures has increased steadily in the last decade, owing to a shift in emphasis forward sustainability and low carbon emission of the construction industry. This increased interest and the growing number of researchers and institutions active in this field are the motivation for the setting of COST ACTION FP1101 on assessment, reinforcement and monitoring of timber structures, now nearing completion of its second year of activity. The paper explains what a COST Action is and presents the aims and objectives of this European Research network initiative. It discussed the state of the art in these three fields of research activities as outlined by the work developed jointly by the network. It discusses avenues for further international collaboration beyond Europe by using some of the implementation instruments available within the COST framework. The paper concludes with a discussion on the current research gaps identified through the network workshop, and a view as to how the major outcomes of the network activities can be further disseminated and find institutional outputs through collaboration with RILEM and European Standardisation Technical Committees.